Antimicrobial resistance in humans and livestock population in India - SEN, ARNAB; BANDOPADHYAY, SAMIRAN; MISRI, JYOTI; CHAUHAN, H C; KUMAR, P ANAND; VAID, R K; DUTTA, T K; DUBAL, Z B; SHOME, B R; K SINGH, R; BHATIA, RAJESH; KUMAR, ASHOK; et al. (The Indian Journal of Animal Sciences, 2022)
Antimicrobial resistance (AMR) is considered as one of the biggest threats to modern civilization. The review is published with a view to provide awareness about this growing menace, which if not monitored and controlled could lead to major public health consequences with greater economic impact. Very little data and information is available regarding AMR in livestock and aquaculture. An attempt was made to collate the available information on AMR subsequent to constitution of INFAAR (Indian Network on Fishery and Animals Antimicrobial Resistance) by ICAR and FAO, in reference to National Action Plan on AMR by GoI in April, 2017.